2013
DOI: 10.4028/www.scientific.net/amr.855.245
|View full text |Cite
|
Sign up to set email alerts
|

Impact Sound Insulation Concept for Lightweight Timber Floor

Abstract: This paper is the second continuation of lightweight timber frame floor construction investigation with a respect to impact noise isolation. We will log on to previous article which dealt with mockup investigation of new LWTF floor conception. The main objectives of research is to design lightweight floor with good impact sound insulation performance to achieve low cost and reduce thickness of construction. In the following chapters well outline results of new floor model on lightweight timber frame constructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…When analyzing the samples with floating floor (S13 to S39), it was observed that there was a decay of sound levels from the 160 Hz band in all samples. This was because it is a typical floating floor system whose vibrational response of the system is sensitively attenuated at the point of primary mechanical excitation (also observed in works such as (MEDVE;INGELEARE;GEETERE, 2014;OLIVEIRA et al, 2021;PARK et al, 2015;PARK;YOON;CHO, 2020).…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…When analyzing the samples with floating floor (S13 to S39), it was observed that there was a decay of sound levels from the 160 Hz band in all samples. This was because it is a typical floating floor system whose vibrational response of the system is sensitively attenuated at the point of primary mechanical excitation (also observed in works such as (MEDVE;INGELEARE;GEETERE, 2014;OLIVEIRA et al, 2021;PARK et al, 2015;PARK;YOON;CHO, 2020).…”
Section: Resultsmentioning
confidence: 96%
“…Light wood flooring systems have better insulation for medium and high-frequency ranges compared to the heavy ones. As a consequence, the low-frequency influence needs to be further investigated (BOLMSVIK; BRANDT, 2013;CANIATO et al, 2015;HIRAMITSU;HASEMI;KAKU, 2014;LJUNGGREN;ÅGREN, 2013;CANIATO et al, 2016;MEDVE;INGELEARE;GEETERE, 2014;QUIRT;NIGHTINGALE;KING, 2006). Moreover, studies show that T-beam/hollow-block slabs present most of the sound transmission in the spaces of the ceramic tiles because they allow the internal reverberation of sound and amplify the sound waves in some central frequency bands (HOPKINS, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The literature review on this topic does not divide effects connected to different structures. The main topics, as previously reported, are the low frequency range effects.Medved et al[82] used a mock-up model to investigate how mass effect interacts with low frequency impact noise, showing how the use of pre-mixed concrete gravel acts better than extra boards as impact sound reduction.Ljunggren and Ågren[83] studied the influence of elasticity in the construction. In order to rise low frequency insulation performance, the use of elastic connections should be introduced.…”
mentioning
confidence: 99%